2020
DOI: 10.1007/jhep12(2020)068
|View full text |Cite
|
Sign up to set email alerts
|

Current and future neutrino oscillation constraints on leptonic unitarity

Abstract: The unitarity of the lepton mixing matrix is a critical assumption underlying the standard neutrino-mixing paradigm. However, many models seeking to explain the as-yet-unknown origin of neutrino masses predict deviations from unitarity in the mixing of the active neutrino states. Motivated by the prospect that future experiments may provide a precise measurement of the lepton mixing matrix, we revisit current constraints on unitarity violation from oscillation measurements and project how next-generation exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 104 publications
(204 reference statements)
1
65
0
Order By: Relevance
“…The unitarity framework is a relatively model independent framework to quantify deviations from the standard three flavor oscillation picture. Investigations into this framework have found that the electron neutrino row is fairly well constrained, the muon neutrino row is relatively well constrained, and that the tau neutrino row is largely unconstrained using a subset of the above data sets [11][12][13]. A new study focused on the tau neutrino row has showed that more data sets than previously used significantly improves the constraints on the tau neutrino row [14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unitarity framework is a relatively model independent framework to quantify deviations from the standard three flavor oscillation picture. Investigations into this framework have found that the electron neutrino row is fairly well constrained, the muon neutrino row is relatively well constrained, and that the tau neutrino row is largely unconstrained using a subset of the above data sets [11][12][13]. A new study focused on the tau neutrino row has showed that more data sets than previously used significantly improves the constraints on the tau neutrino row [14].…”
Section: Methodsmentioning
confidence: 99%
“…That is, while it is known from long-baseline accelerator experiments that since θ 23 ∼ 45 • [8-10], if one does not assume the 3 × 3 lepton mixing matrix is unitary, then on an event-by-event basis every tau neutrino would appear to be indistinguishable from an electron neutrino. These various data sets and their impact on the tau row of the lepton mixing matrix without the assumption of unitarity are discussed in [14] which significantly expands the tau neutrino input beyond previous unitarity analyses [11][12][13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…sin 2 2θ 23 would require at least a statistical uncertainty of a few %, which seems a bit too optimistic (that is, unrealistic) for next, or even next-to-next generation experiments. Nevertheless, studying tau neutrinos with this setup could provide nontrivial information on the unitarity of the PMNS matrix [207][208][209][210][211]. As a final remark, future dark matter direct detection experiments like DARWIN [212] will be able to observe CEνNS from the 8 B solar neutrino flux.…”
Section: Jhep02(2021)097mentioning
confidence: 99%
“…Any scenario beyond the assumption expressed by a different flavor transition matrix could manifest a class of new physics. Typical new physics includes the energy-dependent leptonic mixing matrix [13,14], neutrino-decay [15][16][17][18][19][20][21][22], non-unitary mixing [23][24][25][26][27][28][29][30], pseudo-Dirac neutrinos [31][32][33][34][35][36], neutrino secret interactions [37][38][39][40], etc [41]. These new-physics based transition matrices predict various of flavor ratios of the HAN at Earth.…”
Section: Introductionmentioning
confidence: 99%